Neuropsychological measures of post-COVID-19 cognitive status - Lauria, Alessandra; Carfì, Angelo; Benvenuto, Francesca; Bramato, Giulia; Ciciarello, Francesca; Rocchi, Sara; Rota, Elisabetta; Salerno, Andrea; Stella, Leonardo; Tritto, Marcello; Di Paola, Antonella; Pais, Cristina; et al. (Frontiers in Psychology, 2023)
Background. Covid-19 can cause a number of persistent symptoms during the recovery phase, including cognitive and neurological ones. Aim of this study is to investigate the cognitive and neurological features of patients with confirmed diagnosis of Covid-19 evaluated in the post-acute phase through a direct neuropsychological evaluation. Methods. Individuals recovering from Covid-19 were assessed in an out-patient practice with a complete neurological evaluation and neuropsychological tests (Mini Mental State Examination; Rey Auditory Verbal Test, Multiple Feature Target Cancellation Test, Trial Making Test, Digit span Forward and Backward, Frontal Assessment Battery). Pre- and post-Covid global and mental health status was assessed along with the history of the acute phase of infection. Post-Covid-19 cognitive status was modeled by combining persistent self-reported Covid-related cognitive symptoms and pathologic neuropsychological tests. Results. 406 individuals(average age 54.5±15.1 years, 45.1% females) were assessed on average at 97.8±48.0 days since symptoms onset. Persistent self-reported neurological symptoms were found in the areas of sleep(32%), attention(31%), and memory(22%). MMSE mean score was 28.6. 84 subjects(20.7%) achieved pathologic neuropsychological test results. A high prevalence of failed tests was found in Digit Span Backwards(18.7%), Trail Making(26.6%) and Frontal Assessment Battery(10.9%). Cognitive status was associated to a number of factors including cardiovascular disease history, persistent fatigue, female sex, age, anxiety and mental health stress. Conclusions. Covid-19 is capable of eliciting persistent measurable neurocognitive alterations particularly relevant in the areas of attention and working memory. These neurocognitive disorders were associated with a number of factors: some potentially treatable, others capable of early risk stratification.